PTH-115 Outcome of Ulcerative Colitis Patients that have Failed Conventional Thiopurine Therapy; Allopurinol Co-Therapy and Beyond. (4th June 2013) - Hollingworth, T; Johnson, H; Basuroy, R; Mclaughlin, S; Weaver, S
Abstract : Introduction: Treatments available for Ulcerative Colitis (UC) are limited in those who fail thiopurines. British society of gastroenterology guidelines suggest the use of methotrexate (MTX) or colectomy in this group as biologics are not funded in UC in England or Wales. Clinical treatments used in our unit include low dose thiopurine and allopurinol co-therapy (LDTA) and topical arsenic. We report our experience of patients who have failed standard dose thiopurines and their subsequent treatment and clinical outcomes. Methods: UC patients who failed conventional thiopurine therapy were identified from our prospective inflammatory bowel disease database. Reasons for failure, disease extent, length of follow-up and subsequent treatment pathway were identified. Data from patients with < 3 months follow-up was disregarded. Results: 20 patients were identified, 12 initially started LDTA and 10 started MTX (2 patients received LDTA and then MTX). Mean age was 47 (range: 22–60yrs), 15 were male. 8 had pancolitis, 9 left sided UC and 4 proctitis. Reasons for failure of conventional dose thiopurine were; Hepatitis (n = 5), therapeutic 6-thioguanine levels without clinical remission (n = 11), intolerable side effects (n = 3), dyserythropoeisis (n = 1) and gout (n = 1). Of those patients commenced on LDTA; 10 (83%) entered clinical remission. 2 (17%) failed due to lack of clinical response and commenced MTX. 10 remain in a sustained clinical remission at a mean length of follow up of 16.2 months (range: 4–23). Of the 10 patients commenced on MTX; 7 (70%) failed due to lack of clinical response and 1 (10%) due to side-effects (Pneumonitis). Of those patients that failed; 4 (40%) underwent colectomy, 2 (20%) received arsenic suppositories and entered a sustained clinical remission. 2 (20%) were reclassified to Crohn's disease, were treated with biologic therapy and entered a sustained clinical remission. Mean length of follow up in this group was 17.6 months (range: 2–30). Conclusion: Thiopurines remain the mainstay of treatment for patients with UC. A significant number of patients fail this conventional treatment and represent a clinical challenge. Novel treatments such as LDTA can be effective in a significant proportion of this group. Data for the efficacy of MTX remains less effective and topical arsenic is useful and can be helpful. Disclosure of Interest: T. Hollingworth: None Declared, H. JOHNSON Conflict with: SPONSORSHIP FROM FALK, ABBOTT & WARNER CHILCOTT TO ATTEND MEETINGS, R. BASUROY: None Declared, S. MCLAUGHLIN Conflict with: SPONSORSHIP FROM FALK TO ATTEND MEETINGS, S. WEAVER Consultant for: MSD ADVISORY BOARD, Conflict with: SPONSORSHIP FROM FALK, ABBOT, MSD & FERRING TO ATTEND MEETINGS